Electro-anaerobic digestion as carbon–neutral solutions - Suraj Negi; Jyi-Yong Chai; Audrey Clara Tanesha Tjhin; Shu-Yuan Pan (Chemical and Biological Technologies in Agriculture)
Abstract Electro-anaerobic digestion (EAD) is a promising biowaste treatment technology that integrates a low electric field with conventional anaerobic digestion to enhance biogas yield. Particularly, EAD improves efficiency in CH4 production through enhanced microbial activity and direct electron transfer. This study first illustrates the principles and mechanisms of EAD, and compares with other microbial electrochemical technologies, such as microbial electrolysis, microbial electrosynthesis, and electromethanogenesis. Then, we explore the microbial interactions crucial to biogas production, emphasizing the roles of key bacteria and archaea for CH4 generation in EAD. This study also discusses engineering design considerations for EAD, including applied voltage, temperature, electrode material, electrode spacing, pH control, mixing, and reaction kinetics. The statistical analysis results indicate an average applied voltage of 0.71 V (95% CI 0.48–0.94, n = 19, p < 0.05) and an average CH4 yield of 304.7 mL-CH4 per g-COD (95% CI 252.61–356.73, n = 14, p < 0.05) for EAD operations reported in the literature. Life cycle assessments and techno-economic evaluations reveal that while EAD has higher capital and operational costs than conventional anaerobic digestion, its increased efficiency in CH4 production can offset these costs, resulting in significant long-term economic and environmental benefits. Lastly, this study proposes several priority research directions for EAD, including advancing electron transfer and microbial interactions for system optimization, scaling-up to bridge laboratory success to industrial application, and pioneering carbon–neutral solutions that supports a bio-circular-green economy. Graphical Abstract